2023
DOI: 10.1080/10717544.2023.2174209
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide nanophytosomes exhibit enhanced cellular delivery and pro-apoptotic activities in HepG2 liver cancer cells

Abstract: Andrographolide (AG), a major active constituent of Andrographis paniculata, is known to hinder proliferation of several types of cancer cells. However, its poor solubility and cellular permeability restrict its use in clinical applications. In this study, AG-loaded phytosomes (AG-PTMs) were formulated and optimized with respect to particle size using l -α-phosphatidylcholine (PC):AG ratio and sonication time (ST) as independent variables. The optimized formula was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…These results are consistent with that reported for sorafenib, which significantly inhibits the growth of cancer cells through the accumulation of cells in the pre-G1 phase. 51…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with that reported for sorafenib, which significantly inhibits the growth of cancer cells through the accumulation of cells in the pre-G1 phase. 51…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with that reported for sorafenib, which signicantly inhibits the growth of cancer cells through the accumulation of cells in the pre-G1 phase. 51 These ndings shed light on the mode of action of coumarin derivatives as antiproliferative agents (inducing G0/G1 arrest), which differs from the cytotoxic effect of sorafenib (inducing pre-G1 arrest) and highlight the potential use of coumarins as effective anticancer agents in melanoma treatment. This can be explained by the fact that the G1 phase is a phase that precedes DNA replication, in which the cellular conditions inuence cell cycle progression, causing DNA to either rebuild in a cell or initiate apoptosis, and several studies address the role of G0/G1 phase arrest in intensifying cellular apoptosis.…”
Section: Biologymentioning
confidence: 99%
“…Liver cancer is a major contributor to global cancer-related fatalities, especially in advanced stages with a dismal prognosis. Its high aggressiveness and lethality are often compounded by drug resistance issues [ 25 , 26 ]. Sorafenib, a multikinase inhibitor, has long been the first-line treatment for advanced liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Neamatallah et al, HepG2 cells showed an increased uptake of AG in the phytosomal formulation, resulting in cell cycle arrest in the G2-M phase and increased mitochondrial-dependent apoptosis. Indeed, increased ROS production and decreased MMPs were recorded, as well as an increased expression of Bax and caspase-3 and decreased expression of Bcl-2 [ 132 ].…”
Section: Phytosome and Pathologiesmentioning
confidence: 99%